Metabolic and immune profiles of 1-year and 2.5+ year-old white leghorn roosters following intramuscular lipopolysaccharide injection - Elmore, Kayla M.; Bobeck, Elizabeth A. (Frontiers in Veterinary Science, 2025)
Aerosolized endotoxins such as Lipopolysaccharide (LPS), found in livestock environments, induce an inflammatory mediator cascade. Poultry are commonly exposed to LPS over the growth cycle; however, little is known regarding the cumulative impact of intramuscular LPS injection and its effects on immune cellular metabolism, pathway preferences, and clearance response. Utilizing a LPS model in chickens can offer insight into host immune responses and provide a better understanding of immune tolerance to this endotoxin and major component of Gram-negative bacteria. Therefore, the study objectives were to compare metabolic phenotypes and immune profiles of isolated peripheral blood mononuclear cells (PBMC) from two ages of adult White Leghorn roosters before and post-LPS injection. A total of 20 adult White Leghorn roosters aged 1 yr. or 2.5+ yrs. were randomly assigned to sterile saline or 1 mg/kg body weight LPS (Escherichia coli O55:B5, LPS) injected intramuscularly across 4 sites in breast and thigh muscles. Body weight was recorded before injections at baseline and 24 h post-injection (hpi). Cloacal temperature and blood collections were performed at baseline, 6 hpi, and 24 hpi. PBMC were isolated for Agilent Seahorse XF metabolic analysis and multicolor flow cytometry. Plasma was collected for a C-reactive protein (CRP) enzyme-linked immunosorbent assay. Statistical analysis was performed using the MIXED procedure with fixed effects of age, injection status, and age X injection interaction followed by Tukey–Kramer adjustment (SAS 9.4), with significance denoted at p ≤ 0.05. Aged roosters were found to have fewer CD3+CD8α+ T cells at baseline compared to younger roosters (p < 0.05) while generally displaying delayed immunometabolic changes post-LPS injection compared to younger roosters. Young roosters administered LPS had significantly reduced CRP at 6 hpi compared to control, while aged roosters significantly increased CRP production by 24 hpi (p < 0.05). Both ages responded similarly to inhibitory assays, suggesting that the ability to respond was not different based on age. Overall, results suggest adult roosters may respond differently to LPS injection based on age and immune cell presence, likely due to accumulated exposure to LPS in poultry environments.